Alternative process for gasoline fuel processors - Kale, Ganesh R.; Kulkarni, Bhaskar D. (International Journal of Hydrogen Energy, 2011)
The article explores the thermodynamics of an alternate hydrogen generation process dry autothermal reforming and its comparison to autothermal reforming process of isooctane for use in gasoline fuel processors for SOFC. A thermodynamic analysis of isooctane as feed hydrocarbon for autothermal reforming and dry autothermal reforming processes for feed OCIR (oxygen to carbon in isooctane ratio) from 0.5 to 0.7 at 1 bar pressure under analogous thermoneutral operating conditions was done using Gibbs free energy minimization algorithm in HSC Chemistry. The trends in thermoneutral points (TNP), important product gas compositions at TNPs and fuel processor energy requirements were compared and analyzed. Dry autothermal reforming was identified as a less energy consuming alternative to autothermal reforming as the syngas can be produced with lower energy requirements at thermoneutral temperatures, making it a promising candidate for use in gasoline fuel processors to power the solid oxide fuel cells. The dry autothermal reforming process for syngas production can also be used for different fuels. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Autothermal reforming; Dry autothermal reforming; hydrogen production; Isooctane reforming; Thermodynamic modeling

Factors affecting the production of H-2 by water splitting over a novel visible-light-driven photocatalyst GaFeO3 - Dhanasekaran, P.; Gupta, N. M. (International Journal of Hydrogen Energy, 2012)
A d(10) photocatalyst, GaFeO3 having a band gap of similar to 2.7 eV, exhibits significant activity for the overall splitting of water under visible light (>395 nm) irradiation, in the absence of sacrificial reagent or a noble metal co-catalyst. The doping of an anion led to considerable enhancement in activity, the S-doped catalysts displaying better activity compared to the samples containing nitrogen. Even though the H-2/O-2 yields were affected by preparation-dependent grain morphology, no direct relationship was observed between the photoactivity of a sample and its specific surface area. The techniques of HRTEM, SEM, XPS, Laser Raman, UV-visible and photoluminescence spectroscopy have enabled to demonstrate that, besides the grain morphology, certain lattice imperfections and microstructure may also play a crucial role in water splitting activity of a photocatalyst. The factors responsible for catalyst deactivation are examined. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GaFeO3; hydrogen production; Microstructure; Photocatalyst; water splitting

Covalent organic framework-cadmium sulfide hybrid as a prototype photocatalyst for visible-light-driven hydrogen production - Thote, Jayshri; Aiyappa, Harshitha Barike; Deshpande, Aparna; Diaz, David Diaz; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry A-European Journal, 2014)
CdS nanoparticles were deposited on a highly stable, two-dimensional (2D) covalent organic framework (COF) matrix and the hybrid was tested for photocatalytic hydrogen production. The efficiency of CdS-COF hybrid was investigated by varying the COF content. On the introduction of just 1 wt% of COF, a dramatic tenfold increase in the overall photocatalytic activity of the hybrid was observed. Among the various hybrids synthesized, that with 10 wt% COF, named CdS-COF (90: 10), was found to exhibit a steep H2 production amounting to 3678 mmolh(-1) g(-1), which is significantly higher than that of bulk CdS particles (124 mmolh(-1)g(-1)). The presence of a p-conjugated backbone, high surface area, and occurrence of abundant 2D hetero-interface highlight the usage of COF as an effective support for stabilizing the generated photoelectrons, thereby resulting in an efficient and high photocatalytic activity.
Keywords: charge transfer; covalent organic frameworks; hybrid materials; hydrogen production; Photocatalysis

Enhanced hydrogen fuel production using synergistic combination of solar radiation and TiO2 photocatalyst coupled with Burkholderia cepacia lipase - de Souza Brandao, Luma Mirely; Barbosa, Milson dos Santos; de Jesus, Roberta Anjos; Bharad, Pradnya Arunrao; Lima, Alvaro Silva; Faria Soares, Cleide Mara; Navarro Yerga, Rufino Manuel; Bilal, Muhammad; Romanholo Ferreira, Luiz Fernando; Iqbal, Hafiz M. N.; Gopinath, Chinnakonda S.; Figueiredo, Renan Tavares (International Journal of Hydrogen Energy, 2022)
Promising and sustainable alternatives for hydrogen production have been investigated. Among these, the use of enzymes may represent an efficient alternative. In this work, an increase in hydrogen production under simulated sunlight by combining TiO2 and TiO2/MgCl2 with Burkholderia cepacia lipase (BCL) was reported. The samples (TiO2, TiO2/MgCl2, and TiO2 /MgCl2/BCL) were characterized by X-ray diffraction (XRD), thermo-gravimetric (TGA), N-2 adsorption-desorption isotherms (BET), scanning electron microscopy (SEM), and UV-Visible absorption spectra. Hydrogen production tests were performed in aqueous methanol solutions under simulated sunlight. The results demonstrated that 130-times greater increase in hydrogen production rate was observed by the addition of BCL than individual TiO2. This better hydrogen production rate can be attributed to the increase in the amount of reduction equivalent of the system due to the oxidation of protein peptides caused by TiO2. In conclusion, the results indicate that hydrogen production efficiency can be significantly improved when integrating TiO2/MgCl2 with BCL. (C) 2022 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen production; Lipase; Nano-conjugated enzymes; Photocatalyst; Solar radiation; Titanium dioxide

Mechanistic insight the visible light driven hydrogen generation by plasmonic Au-Cu alloy mounted on TiO2 @B-doped g-C3N4 heterojunction photocatalyst - Babu, Pradeepta; Dash, Soumya Ranjan; Parida, Kulamani (Journal of Alloys and Compounds, 2022)
Designing of two dimensional surfaces and interfaces with light-active materials has been established as a versatile approach to increase their photocatalytic activity. In the present work, n-type anatase TiO2 coupled with p-type B-doped g-C3N4 nanosheet (BCN) were fabricated and Au-Cu nanoalloy with varying atomic ratio were deposited on the p-n heterojunction. The incorporation of Au-Cu on the interface of the dyad enhances light absorption over broad regime, charge separation, and migration. Au-Cu with 1:1 ratio (with an average particle size of 1.2 nm) loaded p-n hetrojunction (TBCAC-1:1) shows excellent photocurrent enhancement (approximately 4.4-folds) in the cathodic direction as compared to their monometallic plasmonic counterpart. Additionally, the catalyst shows photocurrent at zero biased potential as well as lower onset potential as compared to the other alloy. TBCAC-1:1 photocatalyst could able to produce 2150 mu mol h(-1)g(-1) of hydrogen, which is (approximately 3-folds) as compared to their monometallic counterparts. The hydrogen evolution process for Au-Cu (1:1) system was found to be governed by the charge distribution which dictates the binding preference of the Au and Cu sites leading to the water splitting as investigated by DFT calculation. The excellent hydrogen generation by the photocatalyst links to the synergistic effect between Au and Cu associated with the hot electron photochemistry due to surface plasmon resonance phenomenon. (C) 2022 Published by Elsevier B.V.
Keywords: Doped carbon nitride; hydrogen production; LSPR; P-n junction; Photocatalysis; Plasmonic alloy

Morphology-tuned Pt3Ge accelerates water dissociation to industrial-standard hydrogen production over a wide pH range - Mondal, Soumi; Sarkar, Shreya; Bagchi, Debabrata; Das, Tisita; Das, Risov; Singh, Ashutosh Kumar; Prasanna, Ponnappa Kechanda; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (Advanced Materials, 2022)
The discovery of novel materials for industrial-standard hydrogen production is the present need considering the global energy infrastructure. A novel electrocatalyst, Pt3Ge, which is engineered with a desired crystallographic facet (202), accelerates hydrogen production by water electrolysis, and records industrially desired operational stability compared to the commercial catalyst platinum is introduced. Pt3Ge-(202) exhibits low overpotential of 21.7 mV (24.6 mV for Pt/C) and 92 mV for 10 and 200 mA cm(-2) current density, respectively in 0.5 m H2SO4. It also exhibits remarkable stability of 15 000 accelerated degradation tests cycles (5000 for Pt/C) and exceptional durability of 500 h (@10 mA cm(-2)) in acidic media. Pt3Ge-(202) also displays low overpotential of 96 mV for 10 mA cm(-2) current density in the alkaline medium, rationalizing its hydrogen production ability over a wide pH range required commercial operations. Long-term durability (>75 h in alkaline media) with the industrial level current density (>500 mA cm(-2)) has been demonstrated by utilizing the electrochemical flow reactor. The driving force behind this stupendous performance of Pt3Ge-(202) has been envisaged by mapping the reaction mechanism, active sites, and charge-transfer kinetics via controlled electrochemical experiments, ex situ X-ray photoelectron spectroscopy, in situ infrared spectroscopy, and in situ X-ray absorption spectroscopy further corroborated by first principles calculations.
Keywords: Electrochemistry; hydrogen production; intermetallics; water electrolysis

Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT): a 3D sandwiched frameworks with efficient hydrogen production - Kumar, Praveen; Bajpai, Himanshu; Luwang, Meitram Niraj (Journal of Catalysis, 2023)
For over a decade, the structure, reactivity, and mechanism of graphene based photocatalysts have been of great interest for hydrogen (H2) generation. Several studies have been done on the edge side groups (ESGs) of graphene oxide (GO), but the basal plane groups (BPGs)-epoxide and hydroxide have acquired far less attention. This is because the GO layers are strongly held with van der waals forces as well as H-bonding which prevents the foreign body from entering inside the layers. To overcome these problems, this study presents the successful synthesis and application of four coordinated sandwiched (FCS) Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT) in rGO-CdS composite (A 3D sandwiched frame-work). Additionally, experimental outcomes have been further supported using density functional theory (DFT), which suggest that CdOTOT is more stable than its precursors as well as thermodynamically favourable. The CdOTOT shows high H2 production activity -67.5 mmol/g or 13.5 mmol/g/h in presence of 1 % Pt cocatalyst and sacrificial reagents (Na2S/Na2SO3). It is around 33 times higher than pristine CdS, and stable up to around 15 hrs without adding any cocatalyst. This mesmerising outcome is over with reported various CdS-rGO based photocatalysts. The higher activity was further explained through the proposed mechanism and observed low electronic work function of CdOTOT. This innovative and extend-able (with other metals) approach provides a revolutionary impact on numerous cutting-edge research applications like photocatalysis, water splitting, solar cell, etc.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: 2]; 3D sandwiched frameworks; Basal Plane Groups (BPGs); Cadmium (II) Organo Tetrakis-[1; hydrogen production; Oxathiin (CdOTOT)

Chlorophobic iron hydrogen phosphite as OER-active electrocatalyst in anion exchange membrane (sea)water electrolysis - Das, Chandni; Sinha, Nibedita; Nair, Aathira; Pal, Santanu; Joshi, Kavita; Roy, Poulomi (Small, 2025)
Seawater electrolysis is recognized as a promising technology to cater to the worldwide drive for sustainable hydrogen production; however, its practical viability is often hindered by the inevitable anode corrosion arising from the electrode side reactions owing to the presence of high chloride content which eventually degrade the electrode performance eventually. Herein, the design of unprecedented ammonium iron hydrogen phosphite (FeHPhi) along with a trace amount of Cu, is reported as the unique and much desired electrode material for seawater electrolysis due to its special chloride repellant nature along with great electrocatalytic activity toward water oxidation. The [HPO3](2-) oxoanion as Lewis base in the structure effectively restricts chloride ions, while the Fe center acts as Lewis acid offering an active site for water oxidation, also well-supported theoretically. Leveraging this frustrated Lewis pair combination, the electrocatalyst achieves a high current density of 500 mA cm(-2) at 344 mV overpotential in alkaline real seawater with impressive robustness to sustain for 200 h when operated under chlorine evolution reaction dominating region (>2 V). The electrocatalyst also demonstrates superior performance in anion exchange membrane freshwater and seawater electrolysis, demonstrating its potential applicability.
Keywords: AEM electrolyzer; chloride repellant; electrocatalyst; hydrogen production; seawater oxidation

Enhanced electrocatalytic performances of NiCr layered double hydroxides by oxalate intercalation in anion exchange membrane water electrolysis - Pal, Santanu; Sinha, Nibedita; Das, Chandni; Chauhan, Inderjeet; Ahmed, Tanbir; Roy, Poulomi (ACS Applied Materials & Interfaces, 2025)
Layered double hydroxides (LDHs) have attracted much attention these days in the field of water electrolysis due to easy modulation in their layered structure and properties. Herein, NiCr-LDH has been developed, and its interlayer spacing has been considerably increased by oxalate intercalation. Such increased interlayer spacing allows easy access of hydroxides to a large number of electroactive sites and thereby boosts the electrocatalytic performances both for oxygen and hydrogen evolution reactions. Being very active toward both the electrocatalytic reactions, the oxalate-intercalated NiCr-LDH was further explored in an alkaline anion exchange membrane water electrolyzer (AEMWE), achieving 800 mA cm-2 at 1.88 V cell voltage at an operating temperature of 60 degrees C. In fact, the electrolyzer efficiency has been determined to be as high as 69.66%, and the calculated H2 production cost was found to be \$0.97 per gasoline-gallon equivalent, which is well below the targeted cost by the Department of Energy, USA. The electrocatalyst was also examined in harsh alkaline media, like highly saline or seawater, which also indicated its ability to carry out sustainable seawater electrolysis, restricting chlorides to a great extent. Interestingly, post-electrolysis characterization reveals the fact that oxalate decomposition aided carbonate formation within interlayers of NiCr-LDH, and high affinity toward hydroxides is responsible for restricting chlorides during the electrolysis process, apart from the great electrocatalytic activity.
Keywords: Anion exchange; hydrogen production; interlayerspacing; Layered double hydroxide; Sustainable; water electrolyzer

Synthesis of Pd-integrated carbon Dot@TiO2 thin film for photocatalytic glycerol reforming reaction for producing hydrogen - Abraham, Athira; Salgaonkar, Kranti N.; Nivedhitha, Thazhath R.; Ekal, Vishal Ashok; Kondhekar, Deepali; Chakraborty, Shubhankar; Gopinath, Chinnakonda S.; Saha, Avishek (Chemistry-an Asian Journal, 2025)
A series of thin-film photocatalysts comprising TiO2 modified with carbon dots (CDs) dispersed either with palladium (Pd-CD/TiO2) or nickel (Ni-CD/TiO2) were synthesized via solid-state and wet-impregnation methods. Morphological characterization (HR-TEM, SEM-EDS) confirmed the anatase phase of TiO2 and the atomic dispersion of metal-integrated CDs on its surface. UV-vis DRS and XPS analyses revealed a marginal red shift in band-gap and the presence of sp2-hybridized graphitic carbon, and metal-carbon interactions, indicating enhanced light absorption and charge separation through Schottky junctions. Under direct sunlight illumination, Pd-CD/TiO2 thin film exhibited superior hydrogen yield (1167 mu mol g-1 h-1) and maintained stability over 25 h, outperforming Ni-CD/TiO2 (494 mu mol g-1 h-1) and bare TiO2 (166 mu mol g-1 h-1) photocatalyst thin films. Concurrent glycerol oxidation at neutral pH (pH similar to 7) yields glycolaldehyde (41% selectivity), formic acid, and dihydroxyacetone as value-added products. Enhanced photocurrent density and lower impedance of Pd-CD/TiO2 corroborate improved charge carrier separation and dynamics. The results demonstrate that Pd-CD synergistically improves the photocatalytic performance of the Pd-CD/TiO2 for sustainable hydrogen generation and selective biomass valorization.
Keywords: Glycerol oxidation; Graphitic carbon dots; hydrogen production; Photocatalysis; titania